Exploring the Benefits and Drawbacks of Directing Undergraduates' Self-Study Pursuits: An In-depth Analysis through Literature Review - Chin, Pisith; Sam, Rany; Serey, Mardy; Em, Sereyrath (Journal of General Education and Humanities, 2024)
This literature review critically assesses the pros and cons of self-study and self-management, shedding light on their impact on individual learning. The self-study provides flexibility, allowing undergraduate students to customize schedules and fostering autonomy and motivation. However, challenges like maintaining discipline and overcoming isolation are recognized. The review explores psychological benefits, such as improved time management and enhanced problem-solving, alongside drawbacks like procrastination. Affective self-management activities, including goal-setting and active learning, emerge as crucial for self-study success. Future research suggestions include exploring the role of emerging technologies, studying cultural factors, and proposing longitudinal research to assess the sustained effects of self-management activities.